(untitled) (BIRDEM Medical Journal, 2017)
Background: Anemia is common in patients with chronic kidney disease (CKD) and this is generally anemia of chronic disease, but iron deficiency anemia (IDA) is also common. Soluble transferrin receptor (sTfR) is a useful marker for IDA. Present study was undertaken to assess the utility of sTfR as a marker of IDA in selected group of Bangladeshi patients with CKD. Methods: This cross-sectional study was conducted in the Department of Nephrology, BSMMU, Dhaka, Bangladesh from January 2013 to December 2014. Patients with anemia admitted in nephrology department whether on hemodialysis or not and medicine department of BSMMU were taken for study. The study population was further divided into two groups; Group A, patients who are having IDA and Group B, patients with ACD and a control group was also selected. Data were collected by face to face interview and laboratory investigations with a self-administered questionnaire. Results: The mean age of the patients in two study groups were 38.40±13.23 and 34.85±10.52 years respectively and male-female ratio were 0.5:1 and 1:0.5. Mean sTfR level was higher (4.81± 1.64 ?g/ml) in patients with IDA than (2.89±1.40 ?g/ml) in patients with ACD (p <0.0001). In our study mean ferritin level was 599.59± 449.15?g/L in ACD patients whereas 101.23±119.42 in IDA patients (p<0.0001). Total iron binding capacity (TIBC) was more in ACD patients with sTfRe3?g/ml as compared to ACD patients with sTfR<3?g/ml. Transferrin saturation (TSAT) level was significantly decreased in ACD patients with sTfR ?3?g/ml as compared to ACD patients with sTfR<3?g/ml. Conclusion: sTfR has a comparable ability to S. ferritin in diagnosing IDA and ACD. However, sTfR and serum ferritin alone cannot definitely exclude co-existing iron deficiency in ACD. As sTfR is not affected by infection and/or inflammation, thus providing a non-invasive alternative to bone marrow study. Birdem Med J 2017; 7(2): 132-137